Evaluation of Different Rapid Assessment Approaches for Seismic Risk Evaluation of Masonry Structures - Radić, Josip; Işik, Ercan; Hadzima-Nyarko, Marijana (Civil Engineering Journal, 2025)
Masonry structures hold notable historical and cultural significance but exhibit inadequate seismic performance due to low-strength materials and structural limitations. This paper aims to investigate and prioritize the seismic risk of masonry buildings to support preservation strategies, enhance urban resilience, and contribute to sustainability. To achieve this, different rapid assessment methods were comparatively applied, providing a practical alternative to detailed seismic analysis, which was impractical for large building stocks. This study focused on the masonry structures of Osijek, a city characterized by moderate seismic hazard, where these buildings are vital to the cultural heritage, tourism, and identity of the local community. Risk prioritization was conducted for 105 masonry buildings using data collected through systematic field observations and measurements. Findings indicate that while rapid assessment methods provide valuable insights for identifying vulnerable structures, their sensitivity and applicability vary according to building characteristics and the available data. The comparative analysis emphasizes that some methods are more effective at detecting structural deficiencies, whereas others are more suitable for large-scale screening when resources are limited. The novelty of this study lies in identifying the efficiency and limitations of different rapid assessment approaches, thereby advancing knowledge in seismic risk prioritization and providing guidance for heritage protection and disaster risk reduction.